RELATIONSHIP BETWEEN SYSTOLIC BLOOD PRESSURE AFTER INTRAVENOUS ANTIHYPERTENSIVE THERAPY AND OUTCOME OF ACUTE HEMORRHAGIC STROKE - Muhammad Taufiq Regia Arnaz, Yuneldi Anwar & Irina Kemala Nasution (International Journal of Research Science and Management, 2019)
Background: High blood pressure often occurs in patients with hemorrhagic strokes and is associated with poor outcomes and recurrent stroke events. Higher and persistent systolic blood pressure is associated with edema around the bleeding. Methods: Thirty acute hemorrhagic stroke patients who met the criteria were included in this study. All patients received intravenous antihypertensive therapy. The mean systolic blood pressure was obtained by calculating the average of the 30 measurements. Hemorrhagic stroke outcomes were assessed using the Modified Rankin Scale (mRS). Poor outcomes were expressed as mRS values ≥ 3. This study used the Spearman correlation test. Results: There was a significant difference in systolic blood pressure before and after given significant intravenous antihypertensive therapy (p <0.001), but no significant relationship was found between mean systolic blood pressure after receiving intravenous antihypertensive therapy with mRS on day 14 (r = 0.216, p = 0.251) and no significant relationship was found between systolic blood pressure difference before and after receiving intravenous antihypertensive therapy with mRS on day 14 (r = 0.074, p = 0.699). Conclusion: There is no relationship between systolic blood pressure after receiving intravenous antihypertensive therapy with acute hemorrhagic stroke outcome.